Role of Landlords in Creating Healthy Homes: Section 8 Landlord Perspectives on Healthy Housing Practices. Issue 6 (November 2017) - Polletta, Valerie L.; Reid, Margaret; Barros, Eugene; Duarte, Catherine; Donaher, Kevin; Wensley, Howard; Wolff, Lisa
Purpose: This article presents qualitative research findings of Section 8 landlord perceptions regarding healthy housing practices to inform landlord-focused initiatives. Approach or Design: Five focus groups were conducted with landlords. Setting: Boston, Massachusetts. Participants: Section 8 landlords participated in focus groups (n = 39). Method: Focus group transcripts were coded for key themes using a grounded theory approach. Results: Landlords' primary challenges to creating a healthy housing environment included tenant behavior, financial burden, and policy enforcement; tenant safety and cost savings were seen as primary benefits. Conclusion: Landlords play a critical role in implementing healthy housing practices. Several opportunities exist to reduce barriers and capitalize on perceived benefits of implementing these practices, including increasing access to educational and financial resources.